2009
DOI: 10.1021/ja902829p
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of C−N Bonds in Aniline Derivatives on a Ruthenium Center and Its Relevance to Catalytic C−C Bond Formation

Abstract: The first observation of cleavage of unactivated aromatic C-N bonds on a late-transition-metal center was achieved using o-acylanilines and a ruthenium complex. Use of olefins as additives dramatically improved the rate of C-N bond cleavage. The carbon fragment remaining on the ruthenium after C-N bond cleavage was coupled with a phenylboronate to form a biphenyl framework. The present results suggest that ruthenium-catalyzed C-C bond formation from o-acylaniline and organoboronate proceeds via direct C-N bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(36 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…3 More recently, Kakiuchi and co-workers devised a ruthenium-catalyzed C–C coupling reaction of arylamines with organoboranes, by exploiting a directing group assisted sp 2 C–N bond activation strategy. 4 A few remarkably efficient amide-to-ester conversion methods via amide C–N bond cleavage have been achieved by using Ni catalysts. 5 A number of Pd-catalyzed C–N cleavage methods have also been developed, including intramolecular Heck-type coupling reactions 6 and allylamine coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…3 More recently, Kakiuchi and co-workers devised a ruthenium-catalyzed C–C coupling reaction of arylamines with organoboranes, by exploiting a directing group assisted sp 2 C–N bond activation strategy. 4 A few remarkably efficient amide-to-ester conversion methods via amide C–N bond cleavage have been achieved by using Ni catalysts. 5 A number of Pd-catalyzed C–N cleavage methods have also been developed, including intramolecular Heck-type coupling reactions 6 and allylamine coupling reactions.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the bond energies of the C-N bonds are lower throughout the cross-linked network of the epoxy matrix; thus, these bonds are more likely to break rst during the pyrolysis process. 27 Moreover, the Zn 2+ ions in molten ZnCl 2 can form organometallic complexes with C-N bonds aer the resin matrix is swollen; [28][29][30][31][32] this chemical action can promote the fracture of carbon-nitrogen bonds and thus plays a catalytic role in accelerating the degradation of the epoxy matrix. As a result, the chain scission positions of the resin with ZnCl 2 were more concentrated at the C-N bonds.…”
Section: Analysis Of the Degradation Productsmentioning
confidence: 99%
“…(18), Scheme 2.21). The mode of oxidative addition was investigated by the Chatani group through X-ray crystallographic analysis [76]. By heating the aniline 109 and the Ru catalyst 110 in toluene over 3 days, the authors identified 42% of undesired coordinated product 111 along with 6% of the desired C-N-cleaved intermediate 112 ( The advantages of cross-coupling phenolic derivatives have been discussed in detail in the previous sections.…”
Section: Amines and Alcoholsmentioning
confidence: 99%